2022
DOI: 10.3389/fchem.2022.973313
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in macrocyclic arenes-based fluorescent indicator displacement assays

Abstract: Macrocyclic arenes-based fluorescent indicator displacement assays (F-IDAs) offer a unique and innovative approach to chemosensing, taking molecular recognition in host-guest chemistry to a higher level. Because of their special architecture and versatile host–guest binding properties, macrocyclic arenes, principally calix[n]arenes and, in recent years, pillar[n]arenes, in combination with various fluorophores, are widely used in F-IDAs for the specific and selective sensing of cationic, anionic, and neutral a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The water-soluble corral [5]arene (Figure 1a, right) reported by Guo and Cai et al [8] showed high inclusion ability (~10 11 M -1 ), which arises from the induced fit process based on the structural change of the host molecule associated with the guest inclusion. The CPP-based water-soluble supramolecular host in this study has a rigid macrocyclic framework that allows for the inclusion of up to two cationic guest molecules into the cavity.…”
Section: Ws-[9]mentioning
confidence: 92%
See 3 more Smart Citations
“…The water-soluble corral [5]arene (Figure 1a, right) reported by Guo and Cai et al [8] showed high inclusion ability (~10 11 M -1 ), which arises from the induced fit process based on the structural change of the host molecule associated with the guest inclusion. The CPP-based water-soluble supramolecular host in this study has a rigid macrocyclic framework that allows for the inclusion of up to two cationic guest molecules into the cavity.…”
Section: Ws-[9]mentioning
confidence: 92%
“…https://doi.org/10.26434/chemrxiv-2024-55822 ORCID: https://orcid.org/0000-0001-8860-0745 Content not peer-reviewed by ChemRxiv. License: CC BY-NC-ND 4.0 [6]arene (left) [4] and watersoluble corral [5]arene (right), [8] (b) [8] cycloparaphenylene derivative with two alkoxysulphonate units. [12] (c) Water-soluble [9]cycloparaphenylene derivative containing three hydrindacene units with four carboxylates at the 2,6-positions (This work).…”
Section: In This Regard [N]cycloparaphenylenes ([N]mentioning
confidence: 99%
See 2 more Smart Citations
“…In a minireview paper, Duan et al further summarized recent progresses on FID assays based on macrocyclic arenes ( Duan et al, 2022b ). The authors mainly divided the content to two parts: CA[n]-based FID assays and PA[n]-based FID assays.…”
mentioning
confidence: 99%